Political Will Pemerintah Kabupaten Karawang dalam Pengembangan Usaha Mikro Kecil dan Menengah - Nurmala, Elfa; Purnamasari, Hanny; Adiarsa, Sopyan Resmana (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research discusses the Political Will of the Karawang Regency Government in developing Micro, Small and Medium Enterprises. The aim of this research is to examine and analyze the extent of the political will of the Karawang Government in developing Micro, Small and Medium Enterprises in Karawang Regency. This research uses a literature review method with a qualitative approach. This research was analyzed using the political will theory expressed by Derick W. Brinkerhoff with five indicators, namely initiative, priority, political mobilization, law enforcement and business sustainability. The research results show that the political will of the Karawang Regency Government in depeloving Micro, Small and Medium Enterprises is quite good.